Delivering carrier Ethernet [ extending Ethernet beyond the LAN - Abdul Kasim (New York : McGraw-Hill, 2008)
A practical guide to understanding and deploying Carrier Ethernet technologies. It addresses how Carrier Ethernet is the de facto technology in Service Provider networks
Includes index
Keywords: Ethernet (Local area network system)